2020
DOI: 10.3390/fi12060094
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Epidemic as E-Learning Boost? Chronological Development and Effects at an Austrian University against the Background of the Concept of “E-Learning Readiness”

Abstract: The COVID-19 crisis influenced universities worldwide in early 2020. In Austria, all universities were closed in March 2020 as a preventive measure, and meetings with over 100 people were banned and a curfew was imposed. This development also had a massive impact on teaching, which in Austria takes place largely face-to-face. In this paper we would like to describe the situation of an Austrian university regarding e-learning before and during the first three weeks of the changeover of the teaching system, usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
85
0
26

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(117 citation statements)
references
References 10 publications
6
85
0
26
Order By: Relevance
“…Although the required transfer from "face-to-face" teaching to online learning accelerated the digitalization process in dental education [8,15], the complete changeover showed that students and lecturers had difficulties in preparing in advance for online learning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the required transfer from "face-to-face" teaching to online learning accelerated the digitalization process in dental education [8,15], the complete changeover showed that students and lecturers had difficulties in preparing in advance for online learning.…”
Section: Discussionmentioning
confidence: 99%
“…But also in other countries, digitalization at dental schools has been characterized as a slow process [14]. However, this pandemic does not only create the need but rather may provide the chance to accelerate digital transformation in medical education [8,15]. This could have a positive effect on future dental education even beyond COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Within few days, the COVID-19 pandemic enhanced the role of remote working, e-learning, video streaming, etc. on a broad scale [ 14 ]. In [ 15 ], we can see that the most popular remote collaboration tools are private chat messages, followed by two-participant-calls, multi-person-meetings, and team chat messages.…”
Section: 1 Backgroundmentioning
confidence: 99%
“…Ebner et al suggest assessing the readiness of a university for e-learning by using the "seven S model", i.e., by analyzing strategy, structure, systems, style/culture, staff, skills, and shared value of a university [15]. Finally, the paper explains how a university in Austria has shifted its education process to an internal online platform.…”
Section: Global Education Policiesmentioning
confidence: 99%